THE ECONOMY OF UZBEKISTAN WITH THE DEVELOPMENT OF TOURISM - Sh. A. Ashurova (Journals Park Publishing, 2023)
The tourism sector plays an important role in ensuring the economic development of each country and the well-being of our people, as well as creating new local jobs. In recent years, large-scale reforms have been implemented to rapidly develop this industry, increase the flow of foreign tourists to Uzbekistan, and expand domestic tourism. That is why the experience of Uzbekistan in sustainable human development, the priority attitude to scientific and technological progress, innovative and information technologies, the training of highly qualified and comprehensively developed personnel, their full support and new far-sighted initiatives in the field of tourism and upbringing arouse such interest from neighboring states and their scientific communities.
Keywords: tourism, human development, foreign tourists, rapidly developing of industry, increase the flow of foreign tourists, economic development, tourist infrastructure, offering tourist services to domestic, international tourist markets, beautifying tourist facilities, improving the quality, efficiency of services, raising the level of today's requirements.